2016
DOI: 10.1021/acs.langmuir.6b01912
|View full text |Cite
|
Sign up to set email alerts
|

DPPTE Thiolipid Self-Assembled Monolayer: A Critical Assay

Abstract: Supported lipid membranes represent an elegant way to design a fluid interface able to mimic the physicochemical properties of biological membranes, with potential biotechnological applications. In this work, a diacyl phospholipid, the 1,2-dipalmitoyl-sn-glycero-3-phosphothioethanol (DPPTE), functionalized with a thiol group, was immobilized on a gold surface. In this molecule, the thiol group, responsible for the Au-S bond (45 kJ/mol) is located on the phospholipid polar head, letting the hydrophobic chain pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…1 mM solution of DPPTE was prepared by dissolving the powder in chloroform and the gold substrates (AuNPs, gold layer and Au nanoantennas, separately) were incubated into the lipid solution at room temperature (25 °C) for 18 h. After 18 h of immersion, the gold substrates were carefully rinsed with chloroform (~99.9% grade) to remove physically adsorbed phospholipids from the surface, and then dried under a gentle argon flow. The immobilization procedure used here was similar to that one reported by Raffaella Lettieri et al [ 21 ].…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…1 mM solution of DPPTE was prepared by dissolving the powder in chloroform and the gold substrates (AuNPs, gold layer and Au nanoantennas, separately) were incubated into the lipid solution at room temperature (25 °C) for 18 h. After 18 h of immersion, the gold substrates were carefully rinsed with chloroform (~99.9% grade) to remove physically adsorbed phospholipids from the surface, and then dried under a gentle argon flow. The immobilization procedure used here was similar to that one reported by Raffaella Lettieri et al [ 21 ].…”
Section: Methodsmentioning
confidence: 81%
“…The RMS roughness increases from approximately 0.36 ± 0.01 to 1.5 ± 0.3 nm with the appearance of a nanotextured surface after chloroform rinsing, thus confirming the deposition of DPPTE lipid. The corresponding cross sectional profile of the nanotextured surface showed the presence of domain with an average height of 7 nm, suggesting the presence of DPPTE bilayer with 3.26 nm in lipid height in all trans configuration [ 21 ]. A previous study showed that DPPTE phospholipids incubated for 18 h in ethanol solution, formed a monolayer on the gold surface [ 21 ], whose thickness (23.5 ± 0.5 Å) is significantly lower than the lipid film obtained in this study by immersion of the gold layer substrate in 1 mM DPPTE chloroform solution for 18 h. The difference in the thickness can be due to the difference in the sample preparation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Langmuir–Blodgett (LB) technique is a simple and low-cost method for the production of layered structures at the air/water interface, the ordering of which can be controlled by mechanical forces. , The LB method is typically applied to amphiphilic compounds, detergents, and lipids, whose conformational and aggregation behavior at the air/water interface has been deeply characterized by experimental methods and molecular dynamics (MD) simulations. Detailed analyses concerning the conformation and the different phases that molecules experience at the air/water interface during an LB isotherm are usually reported by considering amphiphilic molecules like lipids and fatty acid. However, extensive experimental research has also been carried out on Langmuir films formed by “unusual” molecules, like polymers, DNA, liquid crystals, proteins, carbon nanotubes, and inorganic nanostructures. ,, …”
Section: Introductionmentioning
confidence: 99%